Multiagency Approach to Disaster Management, Focusing on Triage, Treatment and Transport - Khorram-Manesh, Amir; Goniewicz, Krzysztof (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Several steps need to be considered in the management of disasters and emergencies. Establishing command and control, with leaders having communication skills, enables sufficient collaboration and engagement with other agencies and offers the opportunity for situational assessments of the incident as well as the ability to achieve a balance between available personnel and material resources and the need for successful management of the incident. Although these steps are necessary for the overall management of the incident, the medical part remains critical at the operational level. The triage, treatment, and transport of patients are vital steps in the management of the victims and influence the overall outcome of an incident. It is, therefore, critical to establish guidelines regarding how victims are triaged, treated, and transported to specialized medical facilities. These are vital parameters in a multiagency approach to disasters and major incidents, in which several organizations with diverse backgrounds, knowledge, limitations, and abilities need to work together. The aim of this issue is to bring researchers and practitioners together to discuss and describe issues and solutions regarding the evidence-based management of victims of disasters and major incidents, with a particular focus on triage, treatment, and transportation. Special consideration should be given to CBRNE events and their influence on the assessment and management of victims.